Analysis of the Performance of the Jakarta Islamic Index (JII) compared to the Composite Stock Price Index (CSPI) - Judijanto, Loso; Muslimat, Ade; Sudarmanto, Eko; Nurhayadi, Willy (Westscience Press, 2025)
This literature review analyzes the performance of the Jakarta Islamic Index (JII) compared to the Composite Stock Price Index (CSPI) in Indonesia, focusing on key factors such as return performance, risk and volatility, market reactions to economic factors, and the role of Shariah compliance. The review highlights that while the JII generally demonstrates lower returns, it offers greater stability, lower volatility, and resilience during economic downturns due to its ethical and Shariah-compliant nature. In contrast, the CSPI, which includes a broader spectrum of sectors, tends to provide higher returns during periods of economic growth but carries higher risk due to exposure to more volatile industries. The JII’s focus on stable and ethical companies makes it an attractive option for risk-averse and socially responsible investors, while the CSPI is more suitable for those seeking higher returns with a higher risk tolerance. The findings suggest that both indices offer distinct advantages depending on investor preferences and market conditions.